EVALUASI EFEKTIFITAS BIMBINGAN TEKNIS UNTUK MENINGKATKAN KAPASITAS PENYULUH DAN PETANI DI KABUPATEN MOJOKERTO - Latifah, Evy; Dewi, Hanik Anggraeni; Kusuma, Indra; Trijaya, Dewi Sekarsari (Jurnal AGRISEP, 2023)
This study aims to evaluate the improvement of knowledge after following technical guidance which consists of several materials on seeding, cultivation and post-harvest handling of sorghum, porang and orchids. Implementation of Technical Guidance was carried out by discourse and discussion methods. This research was conducted from November to December 2021 in Mojokerto Regency. The material was presented included Plant Propagation Technology with Tissue Culture, Certified Porang Seedling Procedures, Sorghum Cultivation, Sorghum as Animal Feed, and Sorghum Processed Technology. This quantitative assessment was chosen to measure the effectiveness of the implementation of technical guidance (Kartika & Simorangkir, 2019). Data was collected using knowledge improvement evaluation by distributing pre-test and post-test questionnaires to assess the enhancement of knowledge among farmers based on the counselling results that had been implemented. The effectiveness of knowledge enhancement among participants in technical guidance was 36.95%, meaning that knowledge enhancement among participants through technical guidance was categorized as quite effective. Thus, technical guidance was quite effective to be sustainable and able to provide positive value for instructors and farmers, especially if the material presented is relevant and in accordance with the improvement of required innovations and their implementation practices.